Analysis of Helicopter-Transported Trauma Patients at a Regional Trauma Center. Issue 6 (June 2018) - Sebastian, Christina; Collopy, Kevin; Clancy, Thomas V.; Acquista, Elizabeth
Our medical center's regional helicopter emergency medical service (HEMS) serves southeastern North Carolina. Judicious HEMS use is vital to ensure that the resource is available for critically injured patients and to reduce morbidity and mortality by providing timely access to definitive care. We reviewed HEMS use, clinical outcomes, and overtriage rates. The data included airlifted trauma patients from January 2004 to December 2012. Of 1210 total patients, 733 were flown directly from the scene (FS) and 477 from referring hospitals (FH). The HEMS catchment area was a 100-mile radius of our trauma center. FS patients were younger and sustained more motor vehicle collisions. FH patients were older and sustained more falls. FS patients required more hospital resources including longer ventilator requirements, intensive care unit (ICU) stay, and hospital stay. For all HEMS patients, there was 92.2 per cent blunt injury, 47.5 per cent required Trauma I or II activation, 31 per cent required mechanical ventilation, and 50 per cent required ICU care. 59.5 per cent of HEMS trauma patients were critically injured (defined as requiring either immediate surgical intervention, immediate ICU admission, or immediate death). The overtriage rate was 1.8 per cent. The emergency department mortality rate was 2.3 per cent and the ultimate mortality rate was 7.5 per cent. Most of the airlifted trauma patients were critically injured, and therefore, HEMS transport was appropriate. However, overtriage was low, suggesting high incidence of undertriage. There should be a lower threshold for HEMS use for trauma patients in our region. More research is needed to determine ideal overtriage and undertriage rates.